Our last days in Barcelona - Cleeton, Chanel (Berkley, 2022)
"When Isabel Perez travels to Barcelona to save her sister Beatriz, she discovers a shocking family secret. Barcelona, 1964. Exiled from Cuba after the revolution, Isabel Perez has learned to guard her heart and protect her family at all costs. After Isabel's sister Beatriz disappears in Barcelona, Isabel goes to Spain in search of her. Joining forces with an unlikely ally thrusts Isabel into her sister's dangerous world of espionage, but it is an unearthed piece of family history that transforms Isabel's life. Barcelona, 1936. Alicia Perez arrives in Barcelona after a difficult voyage from Cuba, her marriage in jeopardy and her young daughter Isabel in tow. Violence brews in Spain, the country on the brink of civil war, the rise of fascism threatening the world. When Cubans journey to Spain to join the International Brigades, Alicia's past comes back to haunt her as she is unexpectedly reunited with the man who once held her heart. Alicia's and Isabel's lives intertwine, and the past and present collide, as a mother and daughter are forced to choose between their family's expectations and following their hearts"--